2010
DOI: 10.1007/s12032-010-9530-3
|View full text |Cite
|
Sign up to set email alerts
|

The CD44+/CD24− phenotype relates to ‘triple-negative’ state and unfavorable prognosis in breast cancer patients

Abstract: Breast carcinomas have been reported to contain a subpopulation of CD44+/CD24- tumor cells with stem cell-like properties. This study investigates the significance of these two molecules in connection with tumor aggression and prognosis. The phenotypic profile of 139 breast carcinomas was investigated in paraffin sections using markers previously associated with stem cell-like properties (CD44, CD24), the "triple-state" (ER, PR, c-erb-B2), and angiogenesis (CD31). Tumors with >10% of CD44 and CD24 cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 44 publications
7
92
1
Order By: Relevance
“…The relevance of CD44 + CSCs function and clinical outcome has been questioned (17,45,46). This work further supports reports from many other groups that CD44 + cells correlate with EMT, unfavorable prognosis, and metastasis of clinical breast cancer (17,20,21,47). In some instances, mice were injected with tumor cells at two different sites.…”
Section: Discussionsupporting
confidence: 79%
“…The relevance of CD44 + CSCs function and clinical outcome has been questioned (17,45,46). This work further supports reports from many other groups that CD44 + cells correlate with EMT, unfavorable prognosis, and metastasis of clinical breast cancer (17,20,21,47). In some instances, mice were injected with tumor cells at two different sites.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, the majority of studies to date have tended to concentrate on CD44 + /CD24 - (13)(14)(15)(16)(17) and there have been few that have examined a larger range of markers in the same cohort. Giatromanolaki et al (18) investigated the significance of these 2 molecules in connection with tumor aggression and prognosis. The phenotypic profile of 139 breast carcinomas was investigated in paraffin sections using markers previously associated with stem cell-like properties (CD44, CD24), the ̔triple-state' (ER, PR, c-erb-B2) and angiogenesis (CD31).…”
Section: Discussionmentioning
confidence: 99%
“…This tumor phenotype appears to be common in basal like tumors (11,12) and in triple negative tumors (13). It has been suggested that tumor cells with a CD44 + CD24 -subpopulation may have a worse clinical behavior (13,14).…”
Section: Introductionmentioning
confidence: 99%